Variable Compilation Techniques, Research Instruments and Data Collection in Quantitative Research - Intan Dwi Permatasari; Halimatus Sa’diyah; Ach Syafiq Fahmi (Penerbit Hellow Pustaka, 2025)
In quantitative research, variables, research instruments and data collection are very important to include. To provide understanding to determine the focus and objectives of research. A researcher will be more helped in conducting research if he arranges the variables correctly, because variables refer to increasing the validity and reliability of a research. The results of this research show that: 1) the definition of variables, research instruments and data collection methods in quantitative research. Variables are targets in research that have varying values. Research instruments are tools used to obtain, process and interpret information obtained from all respondents. Meanwhile, the quantitative data collection method is a systematic way of collecting information that can be measured statistically. 2) Types of variables and data instruments. There are 2, namely discrete variables and continuous variables. The types of quantitative research instruments are structured questionnaires, unstructured questionnaires, semi-structured questionnaires, Likert questionnaires, semantic questionnaires, Guttman questionnaires, interval questionnaires, nominal questionnaires, ratio questionnaires. 3) Quantitative data collection techniques, namely using surveys and experiments, can also use interviews, observation and documentation and adapting existing procedures in quantitative research.